OP0037 Efficacy of tofacitinib after temporary discontinuation in patients with rheumatoid arthritis: analysis of data from open-label long-term extension studies. (12th June 2018) - Kaine, J.; Tesser, J.; DeMasi, R.; Takiya, L.; Wang, L.; Snyder, M.; Fan, H.; Bandi, V.; Wollenhaupt, J.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Given the chronic nature of RA, there may be situations when therapy is temporarily discontinued. It is important to understand loss of response during temporary discontinuation and the ability to regain disease control following treatment reinitiation. Re-establishment of tofacitinib efficacy following temporary discontinuation/reinitiation has been previously demonstrated in patients (pts) with RA participating in the vaccine sub-study of the long-term extension (LTE) study ORAL Sequel. 1 Objectives: To further assess tofacitinib efficacy and safety after temporary discontinuation and reinitiation in pts with RA in LTE studies. Methods: Data were pooled from two open-label LTE studies (NCT00413699 [database lock: March 2017] and NCT00661661 ) of pts with RA who had completed qualifying Phase 1/2/3 index studies. Pts received tofacitinib 5 or 10 mg twice daily as monotherapy or with conventional synthetic disease-modifying antirheumatic drugs. Pts who received continuous tofacitinib for ≥4 months, temporarily discontinued tofacitinib for 14–30 days and then resumed treatment were included in the analysis. Efficacy outcomes were analysed at the pre-interruption visit (≤90 days before discontinuation) and at the post-interruption visit (within 14–42 days of resuming treatment); data from the interruption period were not analysed. Efficacy outcomes included: ACR20/50/70 response rates, mean tender and swollen joint counts, mean C-reactive protein levels and mean DAS28–4(ESR), CDAI, HAQ-DI, Patient Global Assessment of arthritis, Pain and Physician Global Assessment of arthritis scores. Safety was analysed from Day 1 of temporary discontinuation to the post-interruption visit and included adverse events (AEs), serious AEs (SAEs) and discontinuations due to AEs that occurred within the time range. Results: 261 pts met the criteria for temporary discontinuation. Median (range) duration of temporary discontinuation was 19 14–30 days. Pt demographics are shown in table 1. Efficacy outcomes were generally similar at pre- and post-interruption visits (table 2). From Day 1 of discontinuation to the post-interruption visit, AEs, SAEs and discontinuations due to AEs occurred in 142 (54.4%), 29 (11.1%) and 4 (1.5%) pts, respectively. Conclusions: In pts with RA who temporarily discontinued tofacitinib, similar efficacy responses were observed at pre– and post–interruption visits, suggesting that there is no loss of efficacy after temporary withdrawal and reinitiation of tofacitinib. The safety profile was consistent with previous tofacitinib reports in LTE studies over 9 years. 2 References: [1] Kaine J, et al. Arthritis Rheumatol 2017;69(suppl 10):Abstract 424. [2] Wollenhaupt J, et al. Arthritis Rheumatol 2017;69(suppl 10):Abstract 522. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by AG McCluskey of CMC and funded by Pfizer Inc. Disclosure of Interest: J. Kaine Speakers bureau: Bristol-Myers Squibb, Pfizer Inc, J. Tesser Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, R. DeMasi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Snyder Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Fan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, V. Bandi Consultant for: Pfizer Inc through Eliassen Group Inc, J. Wollenhaupt Speakers bureau: Pfizer Inc